1995
DOI: 10.1108/eb039673
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Strategy

Abstract: Few things have been better documented over the past decade than the decline of formal—read big and heavily‐staffed—strategic planning departments. Recently, however, there seems to be a planning renaissance of sorts with smaller, stream‐lined departments cropping up in U.S. companies (see “The New Lean Planning Machine” Business Strategy, July/August 1994). Now there are some new data that are guaranteed to warm the down‐sized, down‐trodden hearts of corporate planners everywhere—especially those looking to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In a similar vein, there is no evidence to suggest that mission statements create a difference in terms of an industrial firm's performance as Bart argued [6]. A few studies gave limited empirical support to the idea that mission statements are valuable and contribute to higher profits [15,16]. The prior studies prevailing in the literature that examine the impact of mission statements on firms' performance can be summarized under two headings.…”
Section: Relevant Literature and Previous Research Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, there is no evidence to suggest that mission statements create a difference in terms of an industrial firm's performance as Bart argued [6]. A few studies gave limited empirical support to the idea that mission statements are valuable and contribute to higher profits [15,16]. The prior studies prevailing in the literature that examine the impact of mission statements on firms' performance can be summarized under two headings.…”
Section: Relevant Literature and Previous Research Evidencementioning
confidence: 99%
“…Based on the responses obtained from U.S. executives to identify visionary companies, it was pointed out that these visionary firms perform better than other companies traded on U.S. stock exchanges. Rarick and Vitton [15] stated that there is a significant positive relationship between having a mission statement and shareholder equity. The average return on shareholder equity for firms with mission statements was 16.1% compared to 9.7% for those without mission statements.…”
Section: Relevant Literature and Previous Research Evidencementioning
confidence: 99%
“…Mission statements have been examined as a key indicator of organizational performance [80][81][82][83][84][85]. Some empirical studies proved that a positive correlation exists between corporate mission statement and corporate performance [86][87][88][89][90].…”
Section: Moderating Role Of Corporate Missionmentioning
confidence: 99%
“…We expected that when fit situation arises, it will impact organisation performance positively. A review of past studies showed that organisation outcomes (OC) are measured regarding reported financial data (Bart & Baetz, 1998;Bart et al, 2001;Pearce & David, 1987;Rarick & Vitton, 1995). However, recently scholars criticise the appropriateness of using financial data to measure outcomes (Desmidt et al, 2011).…”
Section: A Fit Perspectivementioning
confidence: 99%
“…Scholars in the strategic school of thought focus on the strategic arrangement (for examples: policies, procedures, processes, systems and goals) of the organisation conditions to study mission statement effectiveness. These studies intend to show whether differences in the content of the mission statement will influence financial outcomes (Analoui & Karami, 2002;Atrill et al, 2005;David, 1989;Klemm, Sanderson, & Luffman, 1991;Pearce & David, 1987;Rarick & Vitton, 1995). This strategic school is differentiated from the cultural school of thought which view the mission statement as a text document that shapes the values, identity, meaning, and culture of the organisation (Campbell et al, 1992;Desmidt & Heene, 2003;Ledoux, 2005;Swales & Rogers, 1995).…”
Section: Introductionmentioning
confidence: 99%